IMPORTANCE OF USING POLITENESS WORDS IN LITERATURE - Yakubova, Kamola Shokirova; Esanova, Nafosat Faxriddinovna (Educational Research in Universal Sciences, 2023)
The utilization of polite language in literature plays a vital role in establishing a sense of respect and courtesy among characters, as well as between the author and the reader. The use of courteous language aids in conveying the characters’ etiquette, societal standing, and interpersonal connections. Additionally, it contributes to the authenticity and depth of dialogues, rendering the interactions between characters more realistic and relatable to the audience.